HR strategy : creating business strategy with human capital - Kearns, Paul (Amsterdam ; London : Elsevier/Butterworth-Heinemann, 2010)
Focusing on HR as a key driver of competitive advantage and sustainable success, this edition demonstrates how to create a winning human resource strategy by predicting the results you expect to see and developing a workable, measurable plan for managing human capital
1. What is the purpose of HR-business strategy? -- 2. HR-business strategy is a new, generic option -- 3. What does a strategic HR-business look and feel like? -- 4. So what is the best theory on managing people? -- 5. Are you mature enough for HR-business strategy? -- 6. Who will develop the HR-business strategy? -- 7. Strategic value measures and management tools -- 8. What factors have the biggest influence on the value of an HR-business strategy? -- 9. Due diligence and reporting on human capital
Includes bibliographical references and index
Keywords: Human capital; Manpower planning; Personnel management